Additional Cover. (15th December 2021) - Tokita, Tsukasa; Takaya, Tomohisa; Iwata, Koichi
Abstract : The cover image is based on the Special Issue – Research Article Development of a highly stable picosecond time-resolved Raman spectrometer near Fourier‐transform limit with a femtosecond light source by Tsukasa Tokita et al., https://doi.org/10.1002/jrs.6232 .